Berkelakar and Directives in Palembang Malay: The Islamic Humor Discourse in Indonesia (JOURNAL OF INDONESIAN ISLAM, 2021)
This paper identifies cultural-linguistic practices in Palembang Malay humor and directives in Islamic speech in Indonesia. Berkelakar (make a joke), as part of everyday interactions among the people of Palembang, has not previously been examined. This mixed method research, using Partington’s theory of affective face and affiliation alignment, applies discourse analysis to 10 Islamic speeches to explore Palembangnese humor and directives. Humor in the form of kelakar (jokes), puns and abbreviations and directives in the form of advice appear most frequently in the lectures and teachings on Islam. As a result, this paper raises cultural awareness and highlights the tradition of humor for the people of Palembang and for Muslim and other communities across Indonesia.